Indonesian Food Translation Approaches Found in 5-Star Hotel Restaurant Menus in Bali - Kencana, Ni Putu Rena Wahyu; Kuntayuni; Pratama, Agus Darma Yoga (SALEE: Study of Applied Linguistics and English Education, 2025)
This research investigated the translation strategies used to translate Indonesian food menus into English at 5-star hotel restaurants in Bali. It also explored the use of cultural-specific items (CSIs) in these translations. The study employed a qualitative research method, gathering data from the official websites of six different 5-star restaurants in Bali. The primary theoretical framework was Beekman and Callow's "Lexical Equivalence When Things or Events Are Unknown in the Receptor Language" (1974). Additionally, Tang Yingmin's (1981) theory on Cultural-Specific Items (CSIs) was applied to identify and categorize the types of CSIs found in the translations. The findings indicated that the most frequently used translation approach was Equivalence by Modifying a Generic Word, followed by Equivalence by Cultural Substitution and Equivalence by Using a Loan Word. Among the CSIs, ingredients were the most commonly represented category, accounting for 35% of the total. Furthermore, the data revealed that translators not only translated the names of main dishes but also provided additional details about side dishes.